An aggressive case of juvenile ossifying fibroma of the craniofacial skeleton. Issue 5 (September 2018) - da Silva, Luiz Arthur Barbosa; da Silva Rocha, Ondina Karla Mousinho; Rodrigues, Rodrigo Rodrigues; Germano, Adriano Rocha; da Costa Miguel, Márcia Cristina
Abstract: Juvenile ossifying fibroma (JOF) is a rare fibro-osseous neoplasm that develops among the craniofacial bones at an early age. Their aggressiveness added to their high tendency to recur, provoke real diagnostic and therapeutic challenges. We present an agressive case of a nineteen-year-old girl showing facial asymmetry with a large facial mass. The lesion was surgically excised with a satisfactory esthetic result, besides maintenance of the physiological functions. After two years there is no evidence of recurrence of the lesion. Although JOF is a benign lesion, it typically presents aggressive behavior. The high recurrence rates justifies long-term clinical and radiological surveillance.